Optimization of butanol pathway in metabolically engineered Saccharomyces cerevisiae - Karimi, Maryam (My University, 2012)
Rising of energy costs and increased awareness of global warming have inspired production of renewable, biomass-derived chemicals and fuels. The reasons for producing alternatives to ethanol are multiple: ethanol suffers from low energy density, it cannot be piped, and it is costly to distill. Suitable biofuels will require minimal energy to separate them from fermentation broths, be non-toxic to the host micro-organism, and be efficiently produced from a variety of feedstocks. Butanol is a substantially better biofuel than ethanol. In this study, Saccharomyces cerevisiae was chosen as a host for butanol production because it is a genetically tractable, well-characterized organism, the current industrial ethanol producer, and it has been previously manipulated to produce other heterologous metabolites. This study has focused on optimization of the heterologous butanol pathway in S. cerevisiae for production of higher titers of butanol. In the first part of the present research, the butanol pathway is investigated by simultaneous overexpression of biosynthetic genes hbd, crt, ter and adhE2 under regulation of different combinations of the two promoters of yeast genes TEF1 and PGK1 in S. cerevisiae. The first series of strains contains combinations of butanol synthesis genes under different promoters plus overexpression of the ERG10 gene which resulted in the same levels of butanol production. In the second series of strains, butanol genes were cloned under control of different combinations of promoters and were expressed in yeast along with overexpression of ALD6, acsSE, ADH2, and ERG10 to provide the pathway with higher concentration of cytosolic acetyl-CoA. These strains resulted in different production levels of butanol. These results imply the importance of intracellular concentration of acetyl-CoA, i.e. even if the pathway becomes more efficient due to the promoter swap, it is not distinguishable probably due to the limitation in acetyl-CoA concentration, which is assumed to be lower in strains which only contain the ERG10 plasmid. Variations in butanol titer from 7.5 to 26.8 mg/L, demonstrated that controlling different genes under different promoters can influence the microbial production titer. In the second part of the project butanol disappearance in cultivations of the engineered strains and wild type were also investigated and the probability of the usage of butanol as carbon source by yeast was further studied by shake flasks cultivation. The decreasing trend of butanol concentration after the glucose phase could be due to the utilization of it by the cells or in lower quantity due to evaporation from the medium.
Keywords: Bioinformatik och systembiologi; Livsvetenskaper; Bioinformatics and Systems Biology; Life Science